2001
DOI: 10.1093/treephys/21.10.691
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic conductance in aspen (Populus tremuloides) seedlings exposed to low root temperatures

Abstract: Low root temperatures significantly reduced root hydraulic conductivity and increased resistance to water flow through the roots of aspen (Populus tremuloides Michx.) seedlings. Increased resistance to water flow could not be fully explained by the corresponding increase in water viscosity at low temperatures. The shapes of Arrhenius plots of root water flow and the activation energies were dependent on the direction, sequence and extent of temperature change. The Arrhenius plots suggested that the effect of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 22 publications
8
77
0
Order By: Relevance
“…Many reports have emphasized the changes in water relations because water homeostasis is essential for plant survival under this stress condition, and a significant symptom of chilling injury is shoot water deficit resulting from imbalance between water transport and transpiration [2]. It has been well documented that root water transport is sharply suppressed by exposure to low temperature in a number of species, including maize [3][4][5][6], rice [7], bean [8], spinach [9], aspen [10], cucumber and figleaf gourd [11,12]. Some studies have also demonstrated that a decrease in transpiration follows the reduction in root water flow [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have emphasized the changes in water relations because water homeostasis is essential for plant survival under this stress condition, and a significant symptom of chilling injury is shoot water deficit resulting from imbalance between water transport and transpiration [2]. It has been well documented that root water transport is sharply suppressed by exposure to low temperature in a number of species, including maize [3][4][5][6], rice [7], bean [8], spinach [9], aspen [10], cucumber and figleaf gourd [11,12]. Some studies have also demonstrated that a decrease in transpiration follows the reduction in root water flow [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…Low soil temperature is often a major factor restricting the growth and yield of plants even if the soil is not frozen (Bonan, 1992;Wan and Zwiazek, 1999;Wan et al, 2001). In plants that are sensitive to cold soils, growth reduction is accompanied by the reduction of water uptake, which usually starts within a few minutes after the temperature decrease (Bigot and Boucaud, 1996;Lee et al, 2005a).…”
mentioning
confidence: 99%
“…[35]. The increased viscosity at low temperatures is known to decrease rates of water uptake by roots and transport within the plant [36][37][38], and therefore reduces the rate of nutrient transport to the plants via roots in mass flow. Similarly, the transport of nutrient ions from areas of high to low concentration by the process of diffusion is directly influenced by soil temperature.…”
Section: Resultsmentioning
confidence: 99%